Can we develop the "responsible leaders" we need? Any learning from China and Singapore? (Cultura Económica, 2018)
The author proposes that the development of "globally responsible leaders" is a categorical imperative and develops what are the challenges faced by business schools to develop such leaders. Then, he explores whether some learning could possibly be drawn from China and from Singapore, and in the last part, he proposes alternative actions to develop responsible leaders.
Keywords: RESPONSIBLE LEADERS; BUSINESS ETHICS; CHINA; SINGAPORE; GLOBALIZATION